2015
DOI: 10.1016/j.jval.2015.03.476
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of waste in Prescribing, Dispensing, and Medication consumption in the United States

Abstract: A81tool and disseminated it to a self-selected cohort of 11 small primary care practices that had previously achieved PCMH recognition from the NCQA. We assessed the cost of transformation between 2008 and 2011 using the tool. The cost of transformation was divided into four categories: the cost of NCQA patient centered recognition activities, the application cost of obtaining recognition, the cost of changes to practice culture, and the cost of external collaborations. Costs were averaged and weighted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Others [83][84][85][86] have found that costs of drug wasting can be significant, ranging from $185,000 for 543 surgical cases [83] up to $30 billion annually [87]. In an earlier study, Mankes [71], found eliminating larger vial sizes of propofol, by stocking only 20 mL size had a significant reduction in propofol waste.…”
Section: Discussionmentioning
confidence: 99%
“…Others [83][84][85][86] have found that costs of drug wasting can be significant, ranging from $185,000 for 543 surgical cases [83] up to $30 billion annually [87]. In an earlier study, Mankes [71], found eliminating larger vial sizes of propofol, by stocking only 20 mL size had a significant reduction in propofol waste.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cost, one unclaimed prescription is estimated to be $11.50 [8]. In a different study, the estimated cost is $37 per unclaimed prescription [9]. Studies with different demographic groups show different results.…”
Section: Introductionmentioning
confidence: 94%
“…The economic impact of over-prescribed and under-consumed prescription medications (PMs) is becoming an exceedingly challenging phenomenon. In 2012 alone, the total cost of unfilled, abandoned, or unused PMs in the US health care system was conservatively estimated at $14 billion, 1 while another study in 2015 estimated that the total waste of unused PMs in the United States may exceed $117 billion. 2 Coupled with a subsequent assortment of unintended secondary consequences, opioids are perhaps some of the most problematic, overprescribed PMs.…”
Section: What This Study Addsmentioning
confidence: 99%